Comparison of Prognostic Value of Predictors of Mortality in Patients with Cirrhosis and Refractory Ascites: Prognostic Predictors in Cirrhosis - Muzammil, Muhammad; Ullah, Nadeem; Mukhtar, Shahid; Adnan, Muhammad; Aziz, Hassan; Athar, Mumtaz (Pakistan Journal of Health Sciences, 2024)
The Model for End-Stage Liver Disease-Sodium score (MELDNa) has been developed that has a better prognostic value to predict early mortality but has not been frequently used in cirrhotic and refractory ascites patients with recurrent incidences of severe hyponatremia. Objective: To compare the prognostic value of severe hyponatremia, Child-Pugh score, and the model for end-stage liver disease-sodium score in cirrhotic and refractory ascitic patients. Methods: A prospective, observational study was conducted at the Hepatology Department, Bakhtawar Amin Trust Hospital, Multan from March 2023 to March 2024. A total of 200 patients with cirrhosis and refractory ascites undergoing albumin paracentesis twice a month were selected for the study. The 135 patients (after exclusion of preexisting ascites patients) were administered diuretics symmetrically; 50 mg spironolactone and 40 mg furosemide in patients who did not have renal failure and severe hyponatremia. Prognostic scores were recorded and patients were followed up for minimum 3 months. Results: The area under the curve of the Child-Pugh score (0.90, 95% CI: 0.87-0.96) was significantly higher than the MELD score (0.60, 95 CI: 0.51-0.70) and MELDNa (0.75, 95% CI: 0.65-0.79) as a predictor of mortality (p<0.0001). With respect to the etiology of refractory ascites being an independent risk factor of mortality, the cumulative incidence function was highest in patients with hyponatremia (79%; 95% CI: 79-80%) followed by renal failure patients (55%; 95 CI: 54-56%) and patients receiving maximum dose of treatment (28%; 95% CI: 27-29%) (p<0.001). Conclusions: Severe hyponatremia, ineffective diuretic treatment, and Child-Pugh score were risk factors of death in cirrhotic and refractory ascitic patients.